HIV-related stigma and discrimination by healthcare workers in Egypt. (6th January 2022) - Galal, Yasmine Samir; Khairy, Walaa Ahmed; Mohamed, Rahma; Esmat, Gamal; Negm, Mohamed; Alaty, Waleed Hamed Abd; Saeed, Maysaa A; Fouad, Rabab; Elzahaby, Amgad Ali; Zaky, Samy; Sakr, Mohamed A; Cordie, Ahmed
Abstract: Background: HIV-related stigma and discrimination (SAD) have imposed serious adverse health consequences on people living with HIV (PLHIV), including limited access to medical care and delayed diagnosis, which in turn limits the prevention and control of the disease. This study was conducted to explore the stigmatizing attitudes and behaviors of healthcare workers (HCWs) towards HIV patients and PLHIV. Methods: A cross-sectional study targeted HCWs who attended the United Conference of Hepatogastroenterology and Infectious Diseases that was held on 25–28 September 2019 in Cairo governorate. A self-administrated questionnaire was completed by 359 HCWs. Results: The majority of HCWs reported some discriminatory practices when rendering care to HIV patients, with nurses showing the highest significant number of discriminatory practices. A considerable proportion of HCWs reported witnessing HIV-related SAD at their health facilities. Conclusions: HIV-related SAD was prevalent among HCWs. Hence, HIV-related training relevant to the needs of different groups of HCWs is recommended. Provision of infection control supplies to protect against occupational exposure is also needed. The setting and enforcement of anti-stigma policies and guidelines in various healthcare settings are crucial.